Block‐Based Projection Matrix Design for Compressed Sensing. Issue 3 (1st May 2016) - Li, Zhetao; Xie, Jingxiong; Zhu, Gengming; Peng, Xin; Xie, Yanrong; Choi, Youngjune
Abstract : The objective of optimizing a projection matrix is to decrease the mutual coherence between a projection matrix and a basis matrix. In this paper, a novel block‐based method is proposed to design a projection matrix in compressed sensing. Here, the projection matrix is divided into two blocks. The relationship between the two blocks was obtained by reasoning and proving. Theoretical analysis demonstrates that the mutual coherence between the whole projection matrix and the whole basis matrix keeps as good as the mutual coherence between the block matrix and blocked basis matrix. Experimental results show that the proposed method obtains better performance compared to existing methods.